2020
DOI: 10.3390/s20072111
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity Refractive Index Sensor Based on the Excitation of Long-Range Surface Plasmon Polaritons in H-Shaped Optical Fiber

Abstract: In this paper, we propose and numerically analyze a novel design for a high sensitivity refractive index (RI) sensor based on long-range surface plasmon resonance in H-shaped microstructured optical fiber with symmetrical dielectric-metal-dielectric waveguide (DMDW). The influences of geometrical and optical characteristics of the DMDW on the sensor performance are investigated theoretically. A large RI analyte range from 1.33 to 1.39 is evaluated to study the sensing characteristics of the proposed structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…With single mode operation in the vicinity of 1550 nm, they reported a theoretical refractive-index resolution of up to 5 × 10 3 nm/RIU [45]. Gomez-Cardona et al [46] reported an H-shaped micro-structured optical fiber SPR-based biosensor with symmetrical Another possibility in biosensor design using specialty optical fibers is open-structured micro-structured optical fiber sensors in which the grooves can easily be coated with metal, where the analyte is in direct contact with the metal surface [45,46]. Micro-structured H-shaped plasmonic biosensors can be geometrically different from PCFs, a cross-sectional view of generic form of these sensors is illustrated in Figure 17d.…”
Section: Other Pcf-based Plasmonic Biosensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…With single mode operation in the vicinity of 1550 nm, they reported a theoretical refractive-index resolution of up to 5 × 10 3 nm/RIU [45]. Gomez-Cardona et al [46] reported an H-shaped micro-structured optical fiber SPR-based biosensor with symmetrical Another possibility in biosensor design using specialty optical fibers is open-structured micro-structured optical fiber sensors in which the grooves can easily be coated with metal, where the analyte is in direct contact with the metal surface [45,46]. Micro-structured H-shaped plasmonic biosensors can be geometrically different from PCFs, a cross-sectional view of generic form of these sensors is illustrated in Figure 17d.…”
Section: Other Pcf-based Plasmonic Biosensorsmentioning
confidence: 99%
“…Using the H-shaped PCF-based plasmonic biosensor, they reported an analyte RI detection range between 1.33 and 1.49, with a maximum sensitivity of 25,900 nm/RIU at an analyte RI range of 1.47-1.48. Another possibility in biosensor design using specialty optical fibers is open-structured microstructured optical fiber sensors in which the grooves can easily be coated with metal, where the analyte is in direct contact with the metal surface [45,46]. Micro-structured H-shaped plasmonic biosensors can be geometrically different from PCFs, a cross-sectional view of generic form of these sensors is illustrated in Figure 17d.…”
Section: Other Pcf-based Plasmonic Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the PCFs had been employed to design a new generation of either passive and active photonic devices for telecommunications [8][9][10][11][12]. On the other hand, the PCFs had also been implemented in sensor devices with high sensitivity and compact size in diverse and promising real-life applications [10,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%